(untitled) (Bangladesh Journal of Nuclear Medicine, 2026)
Background: 18F-fluorodeoxyglucose (FDG) PET-CT is widely used in oncology but also detects inflammatory processes. Subacute granulomatous thyroiditis usually shows mild-to-moderate FDG uptake; however, intense uptake may mimic malignancy and create diagnostic confusion. Case Report: A 57-year-old woman presented with anterior neck swelling and respiratory distress. Ultrasonography revealed a markedly enlarged, heterogeneous, hypoechoic thyroid with bilateral cervical lymphadenopathy. Contrast-enhanced CT suggested goiter. 18F-FDG PET-CT demonstrated diffuse thyromegaly extending to the parapharyngeal region with intense FDG uptake (SUVmax 30.7) and multiple FDG-avid cervical lymph nodes, raising suspicion of aggressive malignancy. Initial histopathology showed atypical hyperplasia. Subsequent immunohistochemistry confirmed high-grade B-cell non-Hodgkin’s lymphoma (double expressor: c-MYC and BCL2 positive). The patient showed significant clinical improvement after chemotherapy. Conclusion: Intense FDG uptake in the thyroid can pose a diagnostic dilemma between inflammatory and malignant conditions. Histopathology and immunohistochemistry remain essential for definitive diagnosis. Bangladesh J. Nuclear Med. 29(1): 96-99, 2026